Ridge augmentation in an organ transplant patient. Issue 5 (May 2016) - Dalla Torre, D.; Burtscher, D.
Abstract: With the continuing progress in medicine, the number of successful organ transplantations has continued to increase, a fact that also concerns dentists and implantologists. Implantology after organ transplantation remains controversial due to the patient's immunocompromised situation and the corresponding risk of infection. Only a few studies on this topic have been reported, with all of them showing the dental implant success rates in transplant patients to be similar to those in healthy subjects. However, immunosuppression has been identified as a contraindication to bone augmentation. Consequently, there is still a lack of knowledge regarding pre-implantology bone grafting procedures. The following case report describes the use of ridge augmentation and extended bilateral sinus lift procedures in a liver transplant patient. The patient was treated with an implant-supported fixed prosthesis in the upper jaw and was followed up for a total of 28 months after implant insertion. According to the findings presented, pre-implantology augmentation procedures may be performed successfully in immunosuppressed organ transplant patients. Stable peri-implant conditions were shown over a period of more than 2 years. Nevertheless, further investigations are needed to define a safe treatment protocol for these high-risk patients.